Earth and space observation at the German Antarctic Receiving Station O’Higgins - Klügel, Thomas; Höppner, Kathrin; Falk, Reinhard; Kühmstedt, Elke; Plötz, Christian; Reinhold, Andreas; Rülke, Axel; Wojdziak, Reiner; Balss, Ulrich; Diedrich, Erhard; Eineder, Michael; Henniger, Hennes; et al. (Polar Record, 2015)
The German Antarctic Receiving Station (GARS) O’Higgins at the northern tip of the Antarctic Peninsula is a dual purpose facility for earth observation and has existed for more than 20 years. It serves as a satellite ground station for payload data downlink and telecommanding of remote sensing satellites as well as a geodetic observatory for global reference systems and global change. Both applications use the same 9 m diameter radio antenna. Major outcomes of this usage are summarised in this paper. The satellite ground station O’Higgins (OHG) is part of the global ground station network of the German Remote Sensing Data Centre (DFD) operated by the German Aerospace Centre (DLR). It was established in 1991 to provide remote sensing data downlink support within the missions of the European Remote Sensing Satellites ERS-1 and ERS-2. These missions provided valuable insights into the changes of the Antarctic ice shield. Especially after the failure of the on-board data recorder, OHG became an essential downlink station for ERS-2 real-time data transmission. Since 2010, OHG is manned during the entire year, specifically to support the TanDEM-X mission. OHG is a main dump station for payload data, monitoring and telecommanding of the German TerraSAR-X and TanDEM-X satellites. For space geodesy and astrometry the radio antenna O’Higgins significantly improves coverage over the southern hemisphere and plays an essential role within the global Very Long Baseline Interferometry (VLBI) network. In particular the determination of the Earth Orientation Parameters (EOP) and the sky coverage of the International Celestial Reference Frame (ICRF) benefit from the location at a high southern latitude. Further, the resolution of VLBI images of active galactic nuclei (AGN), cosmic radio sources defining the ICRF, improves significantly when O’Higgins is included in the network. The various geodetic instrumentation and the long time series at O’Higgins allow a reliable determination of crustal motions. VLBI station velocities, ...